Math Aiders Mentoring Program as Remedial Class for Low-Performing Learners - Amy B. Belonio; June Rey S. Sulatra (Researchparks Publishing, 2022)
Peer mentoring is one of the strategies used to enhance learners' mathematics achievement. This study developed a mentoring program that trains the potential higher grades high performing learners to become one of the “Math Aiders” to mentor the low performing learners in lower grades. The math aiders underwent a series of exams and training to become a mentor. Each mentor was assigned to three to five learners. This study was conducted in one secondary island school in Western Visayas, Philippines. Eighty (80) Grade 7 learners and twenty (20) “math aiders” were the participants of the study. A quasi-experimental method was used and the participants were grouped into two (2), the non-experimental (teacher only) and experimental group (math aiders and teacher as facilitator). The mentoring program was done after class hours, specifically at five o'clock in the afternoon (the time for the remedial class for low-performing learners). The instrument used was a researcher-made achievement test in Mathematics 7 which underwent validity and reliability testing. The findings of this study revealed that there is a significant increase in mathematics achievement in both interventions. Comparing the posttest between two groups, the learners' mathematics achievement was higher in the math aiders mentoring program group compared to the non-experimental group which is teacher alone instruction. This means that mentoring activity can be utilized as one of the interventions in the remedial classes to address the decrease in learners' achievement in mathematics.